Antecedent Budgeting Affecting Operational Productivity Moderated by Sustainable Development Goals - Agus Dharmanto; Rahmat Prayogo; Josua Panatap Soehaditama; Agustian Zen (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this paper is to provide a deeper insight into the relationship between budget and sustainable development, and how organizations can utilize it to achieve better results in various aspects. This paper uses a qualitative research method with literature related to the variables in this paper, which will look at the implementation of the variables in this paper, the literature comes from international journals with a span of ten years. Integrating sustainable development goals into their budget process, businesses can create a more positive impact on the environment and society and ensure better financial accountability. Adopting a more sustainable approach in budgeting and integrating the principles of the SDGs, businesses can contribute to sustainable development and achieve better operational productivity, while fulfilling their social responsibilities.